THEORETICAL INTERPRETATION OF SPORT AS A SOCIAL INSTITUTION - Кириленко, О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article reveals the content of the institutional approach to the study of sport, its characteristics, structure, function and dysfunction. An analysis of sport as a social institution allows us to consider it as a social organization, structural and functional manifestations of which in modern conditions become more complicated and controversial. In the conditions of globalization, liberalization and humanization of social life sport strengthens its role as through the development of competitively-professional, and recreational areas of development. It creates and deepens the institutional conflict between the values аnd practices of professional and recreational sports, which may resolve on the basis of the transition to the new design of the institutional organization of sport.